Resenha do livro: "The cartographic state maps, territory, and the origins of sovereignty" - Malafaia, Thiago Correa (Conjuntura Austral, 2014)
Resenha do livro: "The cartographic state maps, territory, and the origins of sovereignty", de Jordan Branch. Cambridge University Press, Nova Iorque; 2014; 219 p.; ISBN 978-1-107-04096-0.